Como o sistema de reputação baseado em avaliação mútua é utilizado por participantes provedores da economia compartilhada? - Pacheco Filho, Ulysses Pereira (2018)
In this Master’s thesis, we investigate how reputation systems can interfere on trust building between strangers who are participants in the sharing economy. It can be defined as an economic activity, powered by a technological platform, based on the interactions between providers and users. Our focus is to study how a provider may feel more comfortable lending his asset or providing his time to a stranger. We explore how a system of mutual reputation can be the catalyst for the development of initial trust among strangers. By doing so, we have tried to fill a gap, identified in the literary review, about the use of mutual reputation systems in sharing economy. Since this is based on mutual interference, the theoretical lens of sociomateriality was used, allowing us to analyze the dynamic construction of the reputation systems and its use and the agential cuts related to the incentive and punishment of users of this economy. The empirical part of how the reputation system is used has been done through a single case study where we verify the use of the reputation system of the Uber passenger by the driver on provision of ridesharing services. Through semi-structured driver interviews, documentation analysis and netnography of Facebook’s and WhatsApp’s drivers groups, we were able to identify provider’s profiles with different initial trust requirements. We also identify the strong interference that intermediaries can exert on the usage of the reputation system by creating forms of provider’s oppression. And finally, we identify the result of sociomaterial bricolage when providers adopt new practices of using the reputation system to compensate the idiosyncrasies of intermediaries like Uber. As practical contributions, we emphasize the importance of equal treatment to the players of Sharing Economy platforms. On mutual evaluation reputational systems, the favoring any of the players contaminates the evaluation and the use of the reputation, invalidating it as apparatus of measuring the initial trust. We also emphasize the need to regulate the intermediaries’ behavior, by limiting abuses on information manipulation, provider’s management (providing a right of defense) and abusive pricing practices. There are also several suggestions for enhancing platform capabilities to facilitate the use of the reputation system such as disclosing punishments and incentives to users or what should be evaluated by providers and users after collaboration.